2015
DOI: 10.1016/j.celrep.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Cycle-Regulated Interaction between Mcm10 and Double Hexameric Mcm2-7 Is Required for Helicase Splitting and Activation during S Phase

Abstract: Summary Mcm2-7 helicase is loaded onto double stranded origin DNA as an inactive double hexamer (DH) in G1 phase. The mechanisms of Mcm2-7 remodeling to trigger helicase activation in S phase remain unknown. Here, we develop an approach to detect and purify the endogenous DHs directly. Through cellular fractionation, we provide in vivo evidence that DHs are assembled on chromatin in G1 phase and separated during S phase. Interestingly, Mcm10, a robust MCM interactor, co-purifies exclusively with the DHs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 45 publications
5
66
0
Order By: Relevance
“…1A). Consistent with recent findings (Quan et al 2015;Douglas and Diffley, 2016), mass spectrometry confirmed that these proteins were Mcm4 and Mcm6 and identified Mcm2 as the third protein (Supplemental Table S1). …”
Section: Mcm10 Binds a Conserved Region In The Mcm2 N-terminal Domainsupporting
confidence: 75%
See 2 more Smart Citations
“…1A). Consistent with recent findings (Quan et al 2015;Douglas and Diffley, 2016), mass spectrometry confirmed that these proteins were Mcm4 and Mcm6 and identified Mcm2 as the third protein (Supplemental Table S1). …”
Section: Mcm10 Binds a Conserved Region In The Mcm2 N-terminal Domainsupporting
confidence: 75%
“…Recruitment of Cdc45 or GINS to Mcm2-7 is independent of Mcm10 (Kanke et al 2012;van Deursen et al 2012;Watase et al 2012;Yeeles et al 2015). In contrast, Mcm10 is required for initial DNA unwinding at origins of replication (Kanke et al 2012;van Deursen et al 2012;Watase et al 2012;Yeeles et al 2015) and has been implicated in the separation of the Mcm2-7 double hexamer (Quan et al 2015). It is possible that the double hexamer of the Mcm2-7 complex inhibits DNA unwinding and that Mcm10 activates unwinding by causing double-hexamer separation (Quan et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalent model from in vitro and in vivo studies in budding and fission yeast is that Mcm10 plays a role late in replication initiation where it is required for unwinding of origin DNA and separation of Mcm2-7 double hexamers 10,26-29 In addition to its involvement in DNA replication initiation, Mcm10 has also been shown to promote genomic integrity in human cells, as lack of Mcm10 leads to accumulation of DNA damage and cell cycle arrest 22,30-32 Budding yeast Mcm10 performs some of its genome protection functions by interactions with 9-1-1 checkpoint clamp and other factors implicated in double strand break repair 33,34 …”
Section: Introductionmentioning
confidence: 99%
“…Crucially, during helicase activation, the MCM2-7 DH becomes extensively reorganized: Cdc45 and GINS bind to MCM2-7; the complex is split into two individual hexamers, potentially involving Mcm10 (Quan et al 2015); one DNA strand becomes extruded from each hexamer; and this results in the two CMG complexes encircling ssDNA (Costa et al 2014;Georgescu et al 2017). Importantly, the mechanisms that lead to this MCM2-7 reorganization during initiation of DNA replication are largely unknown.…”
Section: Initiation Of Dna Replicationmentioning
confidence: 99%